The witch and the dead : a wishcraft mystery - Blake, Heather (Blake, Heather. Wishcraft mystery, 2016)
When she discovers a pile of old bones in her Aunt Ve's garage under a mess of memories and forgotten possessions, wish-granting witch Darcy Merriweather must solve a cold case to keep her aunt from doing a spell in prison.